IMPROVING THE CONTENT OF TEACHING THE PHONETICS OF THE UKRAINIAN LANGUAGE IN THE GYMNASIUM - Bakum, Z.P. (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the problem of the content of teaching phonetics in gymnasium, it also gives the analysis of Ukrainian language programs. The article represents methodological recommendations in forming main competences of senior pupils.